Ru‐Catalyzed Switchable N‐Hydroxyethylation and N‐Acetonylation with Crude Glycerol. Issue 8 (5th March 2020) - Xin, Zhuo; Jia, Le; Huang, Yuxing; Du, Chen‐Xia; Li, Yuehui
Abstract: Highly efficient Ru‐catalyzed selective C−C or C−O bond cleavage of polyols (e.g., crude glycerol) for N ‐hydroxyethylation or N ‐acetonylation of amines was achieved through the hydrogen‐borrowing approach. A variety of amines were transformed to the desired amino alcohols/ketones in moderate‐to‐excellent yields, opening up new avenues for generation of oxygenated pharmaceuticals and fine chemicals from renewable raw materials. The use of new redox‐active catalysts containing bisphosphine/thienylmethylamine ligands allows this hydrogen‐borrowing system to be operated selectively under both basic and acidic conditions. Abstract : Have it two ways : Redox catalysts function under both basic and acidic conditions. A new catalytic hydrogen‐borrowing system allows chemoselective N ‐hydroxyethylation or N ‐acetonylation of amines with polyalcohols. Aided by basic or acidic cocatalysts, a variety of amines are converted to the desired amino alcohols/ketones in moderate‐to‐excellent yields.